Roles of socialisation in strengthening the labour-market positions of young entrants - Marosi, Ildikó (Serbian Journal of Management, 2014)
There are explicit, as well as tacit expectations among skills and competencies that are demanded from those newly graduated. My main question of interest is the following: Where do young people learn these skills, knowledge and experience? Present paper is based on literature review and a quantitative research which was conducted among university students aged 18-33, in autumn 2013. The findings prove that a significant part of tacit knowledge is gained through family socialisation, during the process of informal learning rather than via formal education. Hence, family socialisation affects the competence portfolio of young graduates immensely. Present paper endeavours to investigate this influence.